Usefulness of Macroscopic On-Site Evaluation Using a Stereomicroscope during EUS-FNB for Diagnosing Solid Pancreatic Lesions. (18th January 2022) - Ishikawa, Takuya; Ohno, Eizaburo; Mizutani, Yasuyuki; Iida, Tadashi; Uetsuki, Kota; Yashika, Jun; Yamada, Kenta; Gibo, Noriaki; Aoki, Toshinori; Kataoka, Kunio; Mori, Hiroshi; Takada, Yoshihisa; et al.
Abstract : Background/Aims . The usefulness of macroscopic on-site evaluation (MOSE) during endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) has been reported, but a specific method for MOSE has not been established. We aimed to investigate the usefulness of MOSE using a stereomicroscope (S-MOSE) for the diagnosis of solid pancreatic lesions (SPLs). Methods . We reviewed a total of 60 consecutive patients who underwent both S-MOSE and rapid on-site cytopathological evaluation (ROSE) during EUS-FNB between July 2019 and October 2020, and the usefulness of S-MOSE in comparison with histology was evaluated. A 22-gauge Franseen needle was used to perform EUS-FNB in all patients, and only the specimens obtained by the first pass were evaluated. The final diagnosis was based on the surgical specimen or the clinical course consistent with the EUS-FNB results. Results . The final diagnoses of the 60 patients included 45 patients with pancreatic ductal adenocarcinoma, 6 with autoimmune pancreatitis, 4 with mass-forming pancreatitis, 1 with pancreatic metastasis, 2 with pancreatic neuroendocrine tumor, and 2 with intraductal papillary mucinous carcinoma. The histological diagnostic accuracy of the first pass of EUS-FNB was 83.3% (50/60). The agreement between the S-MOSE and the histological diagnosis was 90% (54/60). The positive predictive value of S-MOSE for histological diagnosis was 90.7%, which can be an indicator of when to stop the EUS-FNB procedure. There were no immediate or delayed adverse events reported after the FNB based on the chart and medical visit history review. Conclusion . In the EUS-FNB of SPLs, S-MOSE can be an alternative to ROSE for specimen evaluation and has the potential to shorten the procedure time.